Down-regulation of pituitary receptors for luteinizing hormone-releasing hormone (LH-RH) in rats by LH-RH antagonist Cetrorelix. - Halmos, G (1996)
Antagonists of luteinizing hormone-releasing hormone (LH-RH), unlike the LH-RH agonists, suppress gonadotropins and sex steroid secretion immediately after administration, without initial stimulatory effects. [Ac-D-Nal(2)1,D-Ph(4Cl)2,D-Pal(3)3,D-Cit6,D-Ala10]LH-R H (SB-75; Cetrorelix) is a modern, potent antagonistic analog of LH-RH. In this study, the binding characteristics of receptors for LH-RH in membrane fractions from rat anterior pituitaries were investigated after a single injection of Cetrorelix at a dose of 100 microg per rat. To determine whether the treatment with Cetrorelix can affect the concentration of measurable LH-RH binding sites, we applied an in vitro method to desaturate LH-RH receptors by chaotropic agents such as manganous chloride (MnCl2) and ammonium thiocyanate (NH4SCN). Our results show that the percentages of occupied LH-RH receptors at 1, 3, and 6 h after administration of Cetrorelix were approximately 28%, 14%, and 10%, respectively, of total receptors. At later time intervals, we could not detect occupied LH-RH binding sites. Ligand competition assays, following in vitro desaturation, demonstrated that rat pituitary LH-RH receptors were significantly (P < 0.01) down-regulated for at least 72 h after administration of Cetrorelix. The lowest receptor concentration was found 3-6 h after Cetrorelix treatment and a recovery in receptor number began within approximately 24 h. The down-regulation of LH-RH binding sites induced by Cetrorelix was accompanied by serum LH and testosterone suppression. Higher LH-RH receptor concentrations coincided with elevated serum hormone levels at later time intervals. Our results indicate that administration of LH-RH antagonist Cetrorelix produces a marked down-regulation of pituitary receptors for LH-RH and not merely an occupancy of binding sites.